Insight Into Osseointegration of Nanohydroxyapatite/Polyamide 66 Based on the Radiolucent Gap: Comparison With Polyether-Ether-Ketone - Li, Jianxiao; Peng, Haitao; Chen, Zhiyu; Hu, Chenbo; He, Tao; Li, Hong; Quan, Zhengxue (Frontiers in Materials, 2021)
Spinal fusion cages have been used in spinal fusion surgery for over 20 years. Polyether-ether-ketone (PEEK) cages are one of the most widely used materials. However, an increasing number of clinical and preclinical studies have shown that as a bioinert material the PEEK cage causes implant failure owing to limited osseointegration. The most common complication is a radiolucent zone at the bone-implant interface. Nanohydroxyapatite/polyamide 66 (n-HA/PA66) is a bioactive composite with sufficient load-bearing properties and good osseointegration abilities. However, in the early stage after surgery, a radiolucent gap can also be observed at the margin of the bone-implant interface. To better assess osseointegration performance as a fusion cage and compare the radiolucent gaps between the two materials, PEEK and n-HA/PA66, implants were prepared and implanted into the femoral condyles of adult New Zealand white rabbits to create a line-to-line bone-implant interface model. The interfaces were systematically investigated using X-ray radiography, histological analysis, scanning electron microscopy (SEM), elemental mapping analysis, micro-computed tomography evaluation, and push-out tests at 4, 8, 12, 24, and 52 weeks. Analysis of X-ray films and histological sections indicated a radiolucent gap around the margin of n-HA/PA66 in the early weeks after implantation (4 to 8 weeks). The gap narrowed and decreased gradually at 24 to 52 weeks. Histological analysis and SEM suggested that the formed bone could integrate and adhere in some regions of the implant surface. In addition, a better bone-like apatite layer was formed between the bone and the n-HA/PA66 implant interface than with the PEEK implant. Push-out tests conducted at 24 and 52 weeks to evaluate integrated strength showed that the n-HA/PA66 implants have better bonding strength and sufficient stability, whereas PEEK implants possess poor integrated strength. Therefore, the n-HA/PA66 composite exhibits good osseointegration properties and an improved integrated bone-implant interface.